0093 Work stress measures are associated with health and physical function around the age of retirement: findings from the hertfordshire cohort study. (21st August 2017) - Stevens, Martin; Syddall, Holly; Linaker, Catherine; D'Angelo, Stefania; Walker-Bone, Karen
Abstract : Background: Studies such as Whitehall II have shown that poor psychosocial work conditions are associated with ill health among employees; it is unclear whether these effects persist and affect health in later life. We have addressed this question using data from the Hertfordshire Cohort Study (HCS). Method: 1021 men and 753 women (59–73 years of age) underwent a home interview and clinical examination and completed a social health questionnaire detailing job-strain (JS) and effort-reward imbalance (ERI) in the current or most recent job. Logistic and linear regression were used to compare the health of participants who reported JS and/or ERI with those who reported neither. Results: 61% reported neither JS or ERI whilst 10% reported both. 72% were no longer working. JS/ERI was not associated with cardiovascular outcomes (stroke, ischaemic heart disease, hypertension) or type II diabetes. However, participants who reported both JS and ERI had increased odds of poor physical function (SF-36) in comparison with those who reported neither (odds ratios: 2.3 [95%CI 1.5, 3.7] men; 2.0 [95%CI 1.2, 3.6] women). Average grip strength was 1.7 kg [95% CI 0.2, 3.3] lower among men who reported both JS and ERI compared to those reporting neither. Similarly, participants reporting both JS and ERI had poorer SF-36 mental health in comparison with those reporting neither (odds ratios: 2.8 [95%CI 1.8, 4.4] men; 3.1 [95%CI 1.8, 5.3] women). Conclusions: JS and ERI in combination are associated with poor physical and mental health outcomes in later life. Further prospective research is required to determine the causal chain of these associations.